The missing link: how HRM systems relate to how people look to the organization - Gomes, Jorge F. S.; Chaves, F. M. R.; Cunha, Rita Campos e; Coelho, Joaquim Pinto (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Strategic human resource management directs attention to the ways in which the HRM system is critical to organisational effectiveness. The relationship between the HRM function and organisation strategy has prompted a strong theoretical interest in the last decades, and it has also had some support from empirical studies. The movement is likely to increase in the forthcoming years. Notwithstanding the theoretical and empirical support to the HRM-organisational performance connection, there is still a significant lack of knowledge with regards to how such association works. Several authors have called for the need to open up the black box, in order to understand the obscure associations between HRM, strategy, and performance (see e.g., Becker and Gerhart, 1996). A novel concept introduced by Bowen and Ostroff (2004) is that of strong HR systems. In such systems, messages regarding what is appropriate behaviour are communicated to employees in an unambiguous and consensual way. Hence, HR systems must possess a set of unique features, which relate to the process by which a consistent message about HR content is sent to employees. HR strength affects the way people interpret their surrounding situations, and weaker HR systems lead to weaker situations. The current research explores the associations discussed above. Data was collected via questionnaire in four companies. Results show good reliability estimates of the new instrument, and they also show associations between situation strength measures and HR strength attributes. The small number of questionnaires received limited deeper analysis. Interpretation and discussion of results lead to more questions than definite answer.